Situation Report: Bulgaria, 24 May 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Changes in the Government / by Rada Nikolaev Tightening of Antiterror Legislation / by Rada Nikolaev Serious Setbacks in Economic Development Admitted / by Rada Nikolaev Private Plots: Success for Private Initiative? / by Rada Nikolaev New Regulations on Scholarships / by Deana Tosheff The Faded Glory of the Morning Star / by Rada Nikolaev